Influence of low-gluten grain crops on beer properties - Koshova, Valentina; Mukoid, Roman; Parkhomenko, Anastasia (My University, 2020)
Показано перспективи використання гречки та гречаного солоду для виробництва низькоглютенового пива

The prospects of using buckwheat and buckwheat malt for the production of low-gluten beer are shown
Keywords: кафедра біотехнології продуктів бродіння і виноробства; пиво; сусло; глютен; гречана крупа; ячмінь; солод; beer; wort; gluten; uckwheat; barley; malt